The Meta Analysis in Public Relations Theory in the Era 1.0, 2.0, 3.0, 4.0, and Artificial Intelligence - Darmastuti, Rini; Winarso, Sri; Christianto, Erwien; Klangrit, Suriya; Mayopu, Richard G. (Komunikator, 2024)
This research delves into the evolution of public relations theory from 1964 to 2024 using a meta-analysis approach and bibliometric techniques. By examining 12,186 articles from the Scopus database, we chart the development of PR theory across five distinct phases: 1.0 (1964-1980), 2.0 (1981-1990), 3.0 (1991-2000), 4.0 (2001-2010), and 5.0 (2011-2024). Our research demonstrates a transition from Traditional one-way communication methods to interactive, data-driven strategies that integrate artificial intelligence. Notable trends include the increasing significance of digital platforms, social media, and AI-driven analytics in public relations. This study offers valuable perspectives on the evolving nature of public relations theory and practice, emphasizing the industry's ability to embrace technological progress and meet changing societal demands. As a result of this analysis, we provide an overview of the main themes, emerging trends, and shifting patterns in PR theory over time, providing a basis for future research in the era of AI-driven Public Relations.